Penerapan Nilai-nilai Kecerdasan Spritual dalam Meningkatkan Motivasi Belajar pada Mahasiswa UIN Sumatera Utara Medan - Hayati, Riska; Hasibuan, Muhtadiah; Nasution, Syawaluddin (Universitas Islam Negeri Raden Intan Lampung, 2024)
Higher education does not only focus on intellectual development, but also aims to build students' spirituality so that they are able to face academic and life challenges wisely. However, low learning motivation due to academic pressure, anxiety, and lack of awareness of spiritual values are significant problems among students at UIN Sumatera Utara Medan, especially in the Communication and Broadcasting Study Program. This study uses a descriptive qualitative approach that is exploratory in nature, with an ethnographic approach, case studies, and phenomenology. Data were collected through interviews, observations, and document analysis. Data processing involves the stages of data reduction, data presentation, and inductive conclusion drawing. The results of the study indicate that the application of spiritual intelligence values containing the principles of Maqashid Syariah has a significant impact on increasing students' learning motivation. Through the application of the values of protecting the soul (hifz an-nafs) and protecting religion (hifz ad-din), students successfully overcome mental obstacles such as anxiety and low self-confidence. In addition, students demonstrate discipline in managing time and energy, and view education as a means of worship and self-development. The application of these values not only improves academic achievement, but also forms the character of students who are more meaningful and oriented towards the good of society.